(untitled) (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2024)
The rapid deployment of large-scale artificial intelligence systems across critical societal domains necessitates architectural frameworks that embed responsibility intrinsically rather than as post-hoc compliance overlays. This study presents a Responsible-by-Design (RbD) architectural paradigm grounded in five core pillars: transparency, fairness, robustness, privacy-preservation, and accountability. We evaluate the RbD framework across three deployment contexts (healthcare decision support, financial risk assessment, and public-sector resource allocation) using a multi-criteria scoring protocol applied to n = 24 architectural configurations. Quantitative analysis reveals that RbD-compliant architectures achieve a mean fairness-score improvement of 34.7% and a robustness index gain of 28.3% relative to baseline systems, while incurring a computational overhead of only 11.4% on average. Findings demonstrate that embedding ethical constraints at the model-design stage substantially reduces downstream bias amplification and adversarial vulnerability without prohibitive performance costs. The paper contributes a reference architecture blueprint, an evaluation rubric aligned with EU AI Act requirements, and empirical benchmarks for responsible AI governance.